Medical Students’ Perspective on the Structure and Standard of Clinical Medical Training in Nigeria: A Survey Across Three Medical Schools in Rivers State, Nigeria - Oyan, Boma; Iroegbu-Emeruem, Linda; Abere, Sarah; Okeke, Uchenna Felicitas; Datubo-Brown, Ibelema; Oparaodu, Ureh; Aria, Oti Nimi; Chris-Biriowu, Bertha; Ijah, Rex Friday Ogoronte Alderton (International Journal of Innovative Research in Medical Science, 2025)
Background: Clinical training is a critical stage of medical education in which medical students gradually acquire skills by interaction with the instructor at the patient’s bedside and apply previously learned concepts in practice. This study aimed to evaluate undergraduate clinical medical students' perspective on medical education at the Rivers State University (RSU), University of Port Harcourt (UPH) and PAMO University of Medical Sciences (PUMS) in Port Harcourt, Nigeria. Methodology: This was descriptive cross-sectional study, and the study population consisted of medical students in the clinical classes - years 4, 5 and 6. Data was collected using a self-administered semi-structured questionnaire distributed via google forms shared on the WhatsApp groups of the classes. Data was exported to and analysed using SPSS version 25. Results: A total of 326 students with a mean age of 22.4±2.4years were recruited and 200(61.3%) were women. While 262 (80.4%) students feel their curriculum is adequate, 66 (20.2%) expressed dissatisfaction with classroom teaching because of poor teaching/communication skills by the lecturers. Feedback with constructive criticism was reported by 298 (91.4%) students, however, 183 (56.1%) reported frequent destructive criticism generally involving hurtful words, insults, and degrading statements. Although 214 (65.6%) students were satisfied with the clinical training, the training was perceived as stressful by 268 (82.2%) students. Conclusion: Clinical training in medical school is stressful, thus identifying and managing the factors that cause this stress is essential as making necessary adjustments in the curriculum will improve the quality of clinical education.